Electronic structure engineering to boost oxygen reduction activity by controlling the coordination of the central metal. Issue 9 (27th June 2018) - Han, Yunhu; Wang, Yanggang; Xu, Ruirui; Chen, Wenxing; Zheng, Lirong; Han, Aijuan; Zhu, Youqi; Zhang, Jian; Zhang, Huabin; Luo, Jun; Chen, Chen; Peng, Qing; et al.
Abstract : FeCl1N4/CNS catalyst first realized a great improvement of ORR by controlling the electronic structure of central metal with coordinated chlorine. Abstract : Adjusting the electronic structure of the active center is a highly effective strategy for improving the performance of catalysts. Herein, we report an atomically dispersed catalyst (FeCl1N4/CNS), which realized for the first time a great improvement of the ORR by controlling the electronic structure of the central metal with a coordinated chlorine. The half-wave potential of FeCl1N4/CNS is E 1/2 = 0.921 V, which is the highest among the reported values for non-precious metal electrocatalysts and far exceeds that of FeN4/CN and commercial Pt/C in alkaline solution. Besides an exceptionally high kinetic current density ( J k ) of 41.11 mA cm −2 at 0.85 V, it also has a good methanol tolerance and outstanding stability. Experiments and DFT demonstrated that the near-range interaction with chlorine and the long-range interaction with sulfur of Fe modulated the electronic structure of the active site, thus resulting in a great improvement of the ORR in alkaline media. The present findings could open new avenues for the design of superior electrocatalysts.